2021
DOI: 10.1039/d0ob01986k
|View full text |Cite
|
Sign up to set email alerts
|

Two-photon uncaging of bioactive thiols in live cells at wavelengths above 800 nm

Abstract: Photoactivatable protecting groups (PPGs) are useful for a broad range of applications ranging from biology to materials science. In chemical biology, induction of biological processes via photoactivation is a powerful...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…In a follow-up study, Distefano and co-workers sought to address this concern, identifying novel caged cysteine 310 in which the methoxy substituent increases the 2PE cross section relative to 306 . A very recent report from the same authors demonstrated the use of a dimethylamine-functionalized NDBF PPG for two-photon uncaging of biologically active thiols in live cells, although this has not yet been applied to cysteine residues …”
Section: Photoactivation Of Biological Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a follow-up study, Distefano and co-workers sought to address this concern, identifying novel caged cysteine 310 in which the methoxy substituent increases the 2PE cross section relative to 306 . A very recent report from the same authors demonstrated the use of a dimethylamine-functionalized NDBF PPG for two-photon uncaging of biologically active thiols in live cells, although this has not yet been applied to cysteine residues …”
Section: Photoactivation Of Biological Functionmentioning
confidence: 99%
“…540 A very recent report from the same authors demonstrated the use of a dimethylamine-functionalized NDBF PPG for twophoton uncaging of biologically active thiols in live cells, although this has not yet been applied to cysteine residues 541. Another class of PPGs that have found widespread use in chemical biology are based on the (coumarin-4-yl)methyl group (311) (Scheme 91).…”
mentioning
confidence: 99%
“…Currently, most PPGs are based on o -nitrobenzyl or coumarinyl scaffolds, ,, which are usually activated by light in the UV region. As UV light may raise risk for DNA damage, particularly with exposure for a prolonged period of time, and have limitations on tissue penetration, PPGs activated by more biologically benign visible and near-infrared (NIR) light are being advanced significantly. , Advantages of photocaged compounds over other pharmacological tools can be recognized in their spatiotemporal confinement, tunability, and reagentless deprotection. In drug discovery, photocaged compounds are highly desirable to reduce the side effects of drugs by precise optical control over the treatment in the targeted disease area . Of particular note, the cascade photocaging concept has emerged in recent years, in which the first PPG is removed upon light irradiation to in turn trigger the release of the second PPG.…”
mentioning
confidence: 99%